Screening of semi‐volatile compounds in plants treated with coated cerium oxide nanoparticles by comprehensive two‐dimensional gas chromatography. Issue 11 (22nd April 2021) - Milenković, Ivana; Radotić, Ksenija; Trifković, Jelena; Vujisić, Ljubodrag; Beškoski, Vladimir P.
Abstract: Literature data about semi‐volatile organic compounds in plants and the effect of cerium oxide nanoparticles on them are scarce. Surface modification of nanoparticles may change nanoparticle‐environment interaction, and therefore affects compounds in plants. In this research, uncoated and glucose‐, levan‐, and pullulan‐coated cerium oxide nanoparticles were used for wheat and pea treatment during the growth. The aim was the screening of semi‐volatile organic compounds from plants' shoots using comprehensive two‐dimensional gas chromatography–mass spectrometry, a powerful separation technique allowing to reach unique separation resolution, and investigation of qualitative changes after the treatment with coated cerium oxide nanoparticles. The results were analyzed by the identification of individual peaks and fingerprint analysis by image processing. Wheat samples contained a higher number of semi‐volatile organic compounds (108) compared to pea (77) but were less affected by the treatments with coated nanoparticles. The highest number of compounds was detected in wheat after the treatment with levan‐ and pullulan‐coated nanoparticles, and in pea after treatment with levan‐coated nanoparticles. This article reports a successful application of a semi‐volatile organic compounds profile presented only as categorical variables and unique fingerprint images for the inter‐cultivar recognition. This method may be useful in screening nanoparticles' effects on different plants.